A series of realist evaluations of multi-component programmes with disengaged young people: What works, for whom, and in what contexts? - EMILY OWEN (2021)
Periods spent in the absence of education, employment, or training (NEET) are associated with adverse psychological wellbeing, poverty, social marginalisation, criminal behaviour, and premature mortality. As such, implementing effective programmes to re-engage young people who are classified, or are at risk of becoming classified, as NEET is of great importance to these individuals, family, and society more broadly. To this end, the aim of the current thesis was to conduct three realist evaluations to understand how and under which circumstances multi-component programmes may impact the engagement, behavioural, and psychosocial outcomes of disengaged students and young people who are not in education, employment, or training. Study 1 consisted of a realist evaluation of a six-month multi-component programme for year ten (aged 14-15 years) disengaged students across three schools. In Study 2, the findings and refined programme theories from Study 1 were subsequently tested through a 10-week multi-component programme with disengaged year eight (aged 12-13 years) students and evaluated over ten months. Informed by the findings from the first two studies, the final study comprised the development, implementation, and evaluation of a four-week multi-component programme utilising appreciative inquiry as a theoretical framework to re-engage young people (aged 17-23 years) who were outside of education, employment, and training. Overall, the findings from the three studies highlighted the potential benefits of utilising a multi-component programme to re-engage young people. Specifically, context-mechanism-outcome configurations and refined programme theories relating to the development of trust, positions of authority, the power of collective experience, exploration of possible life directions, active learning, deviant peer contagion, and the reinforcement and enactment of hegemonic masculine identities were developed. Collectively, the results provide a detailed and practical understanding of the architecture of programmes that can benefit disengaged young people and help advance the implementation of future programmes for working with disengaged populations.